The Impact of Increasing Regional Taxes and Regional Levies on the Original Regional Income (PAD) of Simalungun Regency - Purba, Vebby Anggraeni Novita Sari; Nasution, M. Irsan (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This research examines the influence of local taxes and regional levies on the Original Local Revenue (PAD) of Simalungun Regency during 2019–2023. Employing a quantitative causal approach, the study utilizes secondary data from the Central Bureau of Statistics (BPS) and analyzes it through multiple linear regression. To ensure statistical validity, classical assumption tests such as normality, multicollinearity, autocorrelation, and heteroscedasticity were conducted prior to estimation. The results reveal that both local taxes and regional levies significantly contribute to PAD. Specifically, a 1% increase in local tax revenue enhances PAD by 0.66%, while a 1% rise in regional levies leads to a 12.67% increase in PAD. Together, both factors explain 31.9% of PAD variation, whereas 68.1% is attributed to other sources beyond the model. These findings underscore the importance of strengthening tax collection systems and optimizing levy management to achieve sustainable fiscal capacity at the regional level.